2021
DOI: 10.24996/ijs.2021.62.9.6
|View full text |Cite
|
Sign up to set email alerts
|

Chromogenic in Situ Hybridization for Human Cytomegalovirus-DNA Detection in Tissue Subsets with Prostatic Adenocarcinoma and Benign Hyperplasia

Abstract: Human cytomegalovirus (HCMV) infects a wide range of human cells, resulting in both benign and malignant tumors. In the last few decades, proteins and/or nucleic acids of the virus were found to be often highly expressed in in patients with basal cell hyperplasia and prostatic neoplasia. This research aimed to unravel the rate of HCMV infections among prostatic tissue subsets from Iraqi patients with adenocarcinoma and benign hyperplasia. One hundred, formalin-fixed and paraffin embedded prostatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, it is generally acknowledged that cancer initiation and development, and ALL not being an exception, are caused by a combination of risk factors, such as the interaction of genetic and environmental factors (including oncogenic viruses). It is also suggested that oncogenic viruses encode certain epigenetic factors that lead to the immortality and proliferation of infected cells [12,13]. Abnormal immune responses to infections have been suggested to be implicated in the childhood leukaemia development [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is generally acknowledged that cancer initiation and development, and ALL not being an exception, are caused by a combination of risk factors, such as the interaction of genetic and environmental factors (including oncogenic viruses). It is also suggested that oncogenic viruses encode certain epigenetic factors that lead to the immortality and proliferation of infected cells [12,13]. Abnormal immune responses to infections have been suggested to be implicated in the childhood leukaemia development [14].…”
Section: Introductionmentioning
confidence: 99%